2012
DOI: 10.1074/jbc.m112.392746
|View full text |Cite
|
Sign up to set email alerts
|

Transcription Factor Positive Regulatory Domain 4 (PRDM4) Recruits Protein Arginine Methyltransferase 5 (PRMT5) to Mediate Histone Arginine Methylation and Control Neural Stem Cell Proliferation and Differentiation

Abstract: Background: Neural stem cells generate all the cell types of the central nervous system.Results: Transcription factor, PRDM4, recruits protein arginine methyltransferase 5 (PRMT5) to control the timing of neurogenesis.Conclusion: PRDM4- and PRMT5-mediated histone arginine methylation controls neural stem cell proliferation and differentiation.Significance: Histone arginine methylation is a novel epigenetic mechanism that regulates neural stem cell reprogramming.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
77
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(81 citation statements)
references
References 49 publications
3
77
0
1
Order By: Relevance
“…Its role in preserving the less-differentiated cellular state has been demonstrated in primordial germ cells, erythrocyte progenitors, embryonic stem cells, and neural stem cells [18, 20, 31, 32]. At the molecular level, symmetric dimethylation of arginine R3 on histones by PRMT5 is associated with transcriptional repression of genes involved in neural stem cell differentiation and neuronal lineage determination [33].…”
Section: Discussionmentioning
confidence: 99%
“…Its role in preserving the less-differentiated cellular state has been demonstrated in primordial germ cells, erythrocyte progenitors, embryonic stem cells, and neural stem cells [18, 20, 31, 32]. At the molecular level, symmetric dimethylation of arginine R3 on histones by PRMT5 is associated with transcriptional repression of genes involved in neural stem cell differentiation and neuronal lineage determination [33].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to histones, PRMT5 regulates a number of nonhistone proteins with identifiable functions in RNA processing, translation, signal transduction, apoptosis, and cell cycle regulation. PRMT5 has been shown to maintain pluripotency in both embryonic and adult stem cells and to reprogram mouse embryonic fibroblasts into induced pluripotent stem cells (iPSCs) when introduced with Klf4 and Oct3/4 (12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the study of histone arginine methylation has attracted great attention. Studies have revealed a critical role for this mechanism in epigenetically controlled cellular processes (30) and the functional significance of specific histone methylation (20)(21)(22)(23)31). WDR77 is required for substrate specificity (32), and may define PRMT5-dependent histone methylation targets (22,33,34).…”
Section: Discussionmentioning
confidence: 99%
“…Great attention has been paid to PRMT5-mediated methylation of specific arginine residues in histones. These modifications alter chromatin structure by affecting the recruitment of nonhistone proteins that modulate the accessibility of genomic DNA, thus tuning gene expression involved in cell-cycle progression, differentiation, and DNA repair, among other cellular functions (20)(21)(22)(23). As we recently demonstrated, the highly homologous M7CK phosphorylates specific histone S/T residues, enhancing neighboring lysine acetylation to alter gene expression (9).…”
Section: M6ck Phosphorylates Specific S/t Residues Of Histones and Atmentioning
confidence: 99%